(untitled) (Research, Society and Development, 2021)
This article describes how to deal with home and remote English language teaching with special students during the COVID-19 period. Employing a primarily qualitative research approach, five parents with children diagnosed with autism spectrum disorder were interviewed online. Data were subjected to thematic analysis. The results highlight the following themes: (1) many are better than one at homeschooling during isolation; (2) struggles with the transition to cultivating new activities; (3) new social reality in preparation for the post-pandemic period; (4) all forms of home education are essential; and (5) families encouraging families in these difficult times. This article provides insights into the remote education of children with autism in the midst of the current global emergency.